531 Neuroimaging assessment of unilateral asymptomatic carotid artery stenosis: preliminary results of the carotid artery multi-modality imaging prognostic (camp) study. (8th December 2021) - Masini, Gabriele; Gargani, Luna; Napoli, Vinicio; Cosottini, Mirco; Chiappino, Dante; Orlandi, Giovanni; D'Amelio, Claudio; Totaro, Porzia; Galeotti, Giangiacomo; Palombo, Carlo; De Caterina, Raffaele
Abstract: Aims: Doppler ultrasound (DUS), CT angiography (CTA), and contrast-enhanced MR angiography (CEMRA) are all recommended techniques to evaluate the significance of carotid artery stenosis, although they may give discordant results. Plaque ulcerations may be present, but their role is still controversial. We aimed at assessing the concordance and level of agreement, as well as the prevalence of characteristics related to plaque ulceration and association to patients' characteristics among different imaging diagnostic techniques. Methods and results: Sixty-one patients with unilateral asymptomatic carotid artery stenosis (40–60% detected by DUS), enrolled in the ongoing CAMP study were prospectively evaluated with CEMRA and CTA. The level of agreement was calculated by the weighed kappa test. Plaque ulceration was defined as an intimal defect larger than 1 mm in width or 2 mm in depth, detected by CTA and/or CEMRA. Concordance rate was 71% for DUS–CTA, 51% for DUS–CEMRA, and 66% for CTA–CEMRA. Concordance among all noninvasive techniques was only 45%. Compared with DUS, the stenosis was downgraded by CTA in 17% and by CEMRA in 32% of cases. There was a moderate agreement between DUS–CTA {weighed kappa 0.49 [95% confidence interval (CI): 0.31–0.67]}, while agreement between DUS–CEMRA and CTA–CEMRA was fair [weighed kappa 0.15 (95% CI: −0.01–0.31) and 0.38 (95% CI: 0.14–0.62), respectively]. An ulcerated plaque was present in 39% of patients at CTA and/or CEMRA; compared with patients with non-ulcerated plaques, those with an ulcerated plaque had higher levels of C-reactive protein (CRP), and a trend to higher levels of high sensitivity cardiac troponin (cTn) T (Table), whereas the degree of stenosis was similar. Conclusions: CTA and CEMRA tend to report a lower degree of stenosis compared with DUS. Concordance and level of agreement was higher for DUS and CTA. Plaque ulceration is common and is associated with a significant higher level of systemic inflammation, as detected by CRP and, possibly, cTn.